Determinants of the Degree of Fiscal Sustainability - António Afonso; José Alves; José Carlos Coelho (Center for Economic Studies and ifo Institute (CESifo), 2023)
We assess the link between fiscal sustainability coefficients, namely the responses of the primary government balance and the global government balance to the debt-to-GDP ratio, and the response of government revenues to government expenditures. For 22 OECD developed countries we use annual data between 1950 and 2019. Other determinants of fiscal responses are also studied in the context of quantile regressions. We find that the output gap contributes to increasing fiscal sustainability by positively influencing the responsiveness of the primary and global government balances; the responses of the primary and global government balances to the debt ratio and the response of government revenues to government expenditures depend on the level of the debt ratio. In addition, from the quantile analysis, the influence of the response of government revenues to government expenditures is negative and increasing over the deciles, confirming the existence of a negative cross-relationship between the fiscal sustainability coefficients.
Keywords: C23; H61; H63; E62; 330; fiscal reaction function; fiscal determinants; panel data; quantile regressions